Characterization of a reversible-assembly mechanical metamaterial with an adjustble mechanical property - WU Qi; YANG Yu; LU Yifei; BAO Panpan; WANG Zhigang (Jixie qiangdu)
Lattice structures have become a research highlight in the fields of aviation, aerospace and automobile because of its high specific strength and stiffness. The development of additive manufacturing technology makes it possible to manufacture mechanical metamaterials with complex geometric shapes and special mechanical properties. However, traditional additive manufacturing processes are difficult to coordinate the contradiction between the cost, geometric size and accuracy of such structures.In view of this, a mechanical metamaterial structure concept of reversible assembly and the connection method of its basic voxels were proposed, which can effectively overcome the size limitation of manufacturing equipment, and can construct a macro lattice structure with rich mechanical properties through different combination sequences. Aiming at the basic voxel type of reversible assembly, the influence of voxel geometric parameters, relative density and voxel numbers on its mechanical properties through parametric modeling method was analyzed, and the experimental results were compared. The results show that the three basic voxels have great rigidity difference, and Poisson’s ratio covers the range from negative to positive.Therefore, different combination sequences of these three basic voxels can produce macro structures with different mechanical property distributions, which proves the rationality of using these three basic voxels as the basic voxels of the reversible-assembly structure.In addition, the mathematical relationship between geometric parameters and mechanical properties can provide guidance for the engineering application of such mechanical metamaterials.